An antisense transcript to SMAD5 expressed in fetal and tumor tissues - Zavadil, J; Svoboda, P; Liang, H; Kottickal, L V; Nagarajan, L (Biochemical and biophysical research communications, 1999)
SMAD5, a transducer of TGF-beta/BMP inhibitory signals and a tumor suppressor candidate, localizes to the region of invariant loss in human myeloid neoplasms, on chromosome 5q31.1. Recent evidence indicates a gene-dosage effect along the TGF-beta/BMP signaling pathways. We have identified a novel transcript designated DAMS, whose 3' exonic sequences contain in part an alternate 5' exon of SMAD5, in the antisense orientation. Expressed sequenced tags (ESTs) for DAMS are found in fetal tissues (heart, adrenal glands, and total fetus) and pancreatic tumor cDNA libraries. In contrast to SMAD5, DAMS expression is not readily detectable in adult and fetal tissues. Semiquantitative PCR suggests that the stoichiometry between SMAD5 and DAMS transcripts ranges between 15 and 120 in normal and malignant hematopoietic cells. The findings raise the possibility that DAMS may be a fail-safe mechanism for precise regulation of SMAD5 transcript levels that may be critical in maintaining normal homeostasis.
Keywords: Molecular Sequence Data; messenger RNA; DNA-Binding Proteins; lidské chromozomy, pár 5; protein Smad5; trans-aktivátory; 5' nepřekládaná oblast; Phosphoproteins; RNA nádorová; fosfoproteiny; regulace genové exprese u nádorů; polymerázová řetězová reakce; Polymerase Chain Reaction; hematopoéza; antisense RNA; Tumor Cells, Cultured; Leukemia, Myeloid; Trans-Activators; Transcription Factors; Transcription, Genetic; genetická transkripce; 5' Untranslated Regions; transkripční faktory; Chromosomes, Human, Pair 5; myeloidní leukemie; RNA, Messenger; Humans; Gene Expression Regulation, Neoplastic; Smad5 Protein; RNA dlouhá nekódující; DNA vazebné proteiny; RNA, Neoplasm; molekulární sekvence - údaje; Hematopoiesis; nádorové buňky kultivované; RNA, Long Noncoding; RNA, Antisense; lidé